Investigation of triterpene synthesis and regulation in oats reveals a role for β-amyrin in determining root epidermal cell patterning - Kemen, Ariane C. (National Academy of Sciences, 2014)
Sterols have important functions in membranes and signaling. Plant sterols are synthesized via the isoprenoid pathway by cyclization of 2,3-oxidosqualene to cycloartenol. Plants also convert 2,3-oxidosqualene to other sterol-like cyclization products, including the simple triterpene β-amyrin. The function of β-amyrin per se is unknown, but this molecule can serve as an intermediate in the synthesis of more complex triterpene glycosides associated with plant defense. β-Amyrin is present at low levels in the roots of diploid oat (Avena strigosa). Oat roots also synthesize the β-amyrin–derived triterpene glycoside avenacin A-1, which provides protection against soil-borne diseases. The genes for the early steps in avenacin A-1 synthesis [saponin-deficient 1 and 2 (Sad1 and Sad2)] have been recruited from the sterol pathway by gene duplication and neofunctionalization. Here we show that Sad1 and Sad2 are regulated by an ancient root developmental process that is conserved across diverse species. Sad1 promoter activity is dependent on an L1 box motif, implicating sterol/lipid-binding class IV homeodomain leucine zipper transcription factors as potential regulators. The metabolism of β-amyrin is blocked in sad2 mutants, which therefore accumulate abnormally high levels of this triterpene. The accumulation of elevated levels of β-amyrin in these mutants triggers a “superhairy” root phenotype. Importantly, this effect is manifested very early in the establishment of the root epidermis, causing a greater proportion of epidermal cells to be specified as root hair cells rather than nonhair cells. Together these findings suggest that simple triterpenes may have widespread and as yet largely unrecognized functions in plant growth and development.